Polymers in industry: from guncotton to CO2 glass - Leno Mascia; Domenico Acierno (2012)
The origins of the commercial exploitation of synthetic polymers and the subsequent industrial developments are reviewed, and the main landmarks are highlighted, starting from the pioneering work on the nitration of cellulose in the 19th century and progressing through various advancements to the latest innovations. This includes the contribution made by many authorities, starting from Staudinger, as the founder of polymer science, to the most recent Nobel laureates in the field. The increased awareness for the need to capture CO2 from combustion gases has stimulated interests in the possibility of using polymerization methods as a route to produce useful solid products. The available theoretical arguments and experimental evidence are presented in relation to the feasibility of producing linear polymers, both as homopolymer and copolymers, placing emphasis on stability aspects and possible uses of the products. The various claims on the possibility of opening both double bonds of molecular CO2 to produce stable networks are also analyzed. Arguments in support of the possibilities of producing mixed CO2–SiO2 glasses are provided, and the expected properties of the resulting solids are discussed. Suggestions are made for the possible utilization of such products.